The effects of sphenocentrum jollyanum Pierre root extract on sexual behaviourand hormonal levels in rodents (Journal of Science and Technology, 2016)
Roots of S. jollyanum are considered as sexual stimulant in Ghanaian traditional medicine. The present study is aimed at investigating the effect of an ethanolic extract of the root of S. jollyanum on sexual behaviour of male mice and reproductive hormones in male rats. Extract of S. jollyanum (100, 300 and 1000 mg/kg p.o) stimulated mounting and mating behaviour by increasing mounting frequency, intromission frequency and prolonged ejaculation latency. In addition, a decrease in mounting latency, intromission latency and post-ejaculatory interval was observed. These observations were indicative of increased libido and enhanced sexual behaviour. However, the dose-response curves of some of the parameters measured (attempted mounts, mounting frequency, anogenital sniffing and penile licking) were U-shaped i.e. the effects observed were absent at higher doses. Also the effect of the extract on FSH, LH, prolactin and testosterone levels in rats were determined at weekly intervals for three weeks. Levels of testosterone were increased 4-fold by the third week and there was about 30% increase in FSH levels by the second week which dropped by the third week. Surprisingly, LH levels were reduced by the second week with no significant change in levels of prolactin. These results suggest that there may be more than one mechanism of action of the extract. The immediate increase in sexual behaviour by extract of S. jollyanum may be due to a central stimulatory effect whilst long-term effect might be due to increased testosterone levels. The stimulation of sexual behaviour in male mice and rats supports the claims for its traditional usage in sexual disorders.